Preliminary observations on the bone histology of the Middle Triassic pseudosuchian archosaur Batrachotomus kupferzellensis reveal fast growth with laminar fibrolamellar bone tissue. Issue 4 (4th July 2017) - Klein, Nicole; Foth, Christian; Schoch, Rainer R.
ABSTRACT: The bone tissue of femur, rib, and gastralia from three different individuals of the Middle Triassic pseudosuchian Batrachotomus kupferzellensis from southern Germany is studied. The femoral bone tissue comprises laminar fibrolamellar bone tissue throughout and is stratified by three annual growth cycles, indicating that the individual died early in its fourth year of life, at which time it had reached 87% of maximum known femur length. Thus, compared with most other Pseudosuchia (e.g., phytosaurs, aetosaurs, and most crocodylomorphs, including marine taxa), Batrachotomus achieved its large body size in a very short time by fast, although interrupted, growth and not by protracted longevity. Such fast growth as well as the organization of the tissue is similar to the condition observed in ornithodirans. The pseudosuchians Effigia and Postosuchus also show fibrolamellar tissue, but vascular density is lower when compared with Batrachotomus and dominated by a longitudinal organization of primary osteons. The rib and gastralium of Batrachotomus both show an inner spongious organization surrounded by a ring of compact, avascular, highly organized parallel-fibered and/or lamellar bone largely covered by short fibers. Maximal growth cycle count in the proximal rib sample suggests an age of at least 11 years for this individual with a reduction of growth rate after the sixth cycle.